2021
DOI: 10.1186/s40104-021-00582-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of coding and non-coding RNA transcriptomes related to hypoxic adaptation in Tibetan chickens

Abstract: Background Tibetan chickens, a unique native breed in the Qinghai-Tibet Plateau of China, possess a suite of adaptive features that enable them to tolerate the high-altitude hypoxic environment. Increasing evidence suggests that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) play roles in the hypoxic adaptation of high-altitude animals, although their exact involvement remains unclear. Results This study aimed to elucidate the global landsca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Studies have shown that high-altitude hypoxic environments have an important impact on energy metabolism in animals ( 15 , 20 , 21 ). Similarly, we found many differentially expressed genes and signaling pathways related to glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that high-altitude hypoxic environments have an important impact on energy metabolism in animals ( 15 , 20 , 21 ). Similarly, we found many differentially expressed genes and signaling pathways related to glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA may also play an important role in the adaptability of domestic animals to plateaus. Recent studies have shown that lncRNA is involved in the adaptability of Tibetan chickens and yaks to plateaus; however, the regulatory mechanisms of this lncRNA remain largely unknown ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst avians, chicken has been extensively researched. Studies utilizing sequencing technologies have focused on the roles ncRNAs play in embryogenesis [ 230 ], environmental adaptation [ 231 ], and tissue specific expression [ 232 , 233 ]. Chicken diseases have also received attention with the expression profiles of lncRNAs being studied in avian infectious bronchitis coronavirus (IBV) infected chicken macrophages [ 234 ].…”
Section: Exploring the Ncrna Landscape Beyond Humansmentioning
confidence: 99%
“…Tropomyosin and titin levels were downregulated in yak compared with the three cattle strains, which might facilitate the muscle contraction, since tropomyosin and titin plays an opposite role during the process of muscle contraction [91]. Whole-transcriptome analysis of yak and cattle heart tissues predicted several miRNAs/lncRNAs that are significantly enriched in high-altitude adaptation targeting T cell receptor signaling, VEGF signaling, and cAMP signaling [92] In Tibetan chickens, several key candidate Competing endogenous RNAs (ceRNAs) (DE lncRNAs-DE miRNAs-DE genes), which may play high-priority roles in the hypoxic adaptation of Tibetan chickens by regulating angiogenesis and energy metabolism, were identified [93]. A study which aimed to identify DE genes and novel lncRNAs of yaks for plateau adaptation and their underlying co-expression and regulatory network found a valuable sub-network comprising eight hub genes, one known lncRNA and five novel lncRNAs in the major module.…”
Section: Epigenetic Adaptation Of Animals To High Altitudementioning
confidence: 99%